Production of Anxiety: Transit Places - Lavrinec, Jekaterina (Problemos, 2006)
The discursive production of anxiety that aims at social controlling is analyzed on the base of the concept of the “rhetoric of violence” (M. Foucault). As a case, the transformations in the organization and representation of “transit places” (airports, railway stations, undergrounds, waiting rooms) are examined, claiming, that they have turned into “the space of control” (G. Deleuze). The elements of the “rhetoric of violence” that aim to stimulate social anxiety are in principle undefinable and defy description. Also, it is claimed that imposing some categories, the “rhetoric of violence” deforms the perception of everyday situations.
Keywords: rhetoric of violence; post–structuralism; authority relations; transit places; control